2006
DOI: 10.1109/tns.2006.886042
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gamma and Heavy Ion Damage on the Impulse Response and Pulsed Gain of a Low Breakdown Voltage Si Avalanche Photodiode

Abstract: Effects of displacement and ionization damage on the impulse response of a high-bandwidth low breakdown voltage Si Avalanche Photodiode was investigated using a picosecond laser system. Damage was generated using either Co 60 -irradiation or by scanning the device with an MeV ion microbeam. No shift in the impulse response characteristics and gain was observed for gamma doses as high as 100 kGy(Si). However, dark current measurements for irradiations with biases close to typical operating levels, exhibited enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Displacement damage caused by gamma rays, however, occurs indirectly due to Compton electrons (with a 1.2 MeV maximum energy), but only on a very small scale compared to protons (e.g., [29][30][31]). Si recoil energies can generate a maximum of one or two displaced atoms per scattered electron [32].…”
Section: Co Irradiationmentioning
confidence: 99%
“…Displacement damage caused by gamma rays, however, occurs indirectly due to Compton electrons (with a 1.2 MeV maximum energy), but only on a very small scale compared to protons (e.g., [29][30][31]). Si recoil energies can generate a maximum of one or two displaced atoms per scattered electron [32].…”
Section: Co Irradiationmentioning
confidence: 99%
“…Mounting a PD for integrated charge measurements is much simpler due to relaxation of the aforementioned prerequisites regarding the BW of the external circuit and load. Recent work on pulsed laser injection in Si avalanche photodiodes found them to be ideal candidates for charge contrast [33], since the device gain is extremely sensitive to SC effects.…”
Section: Resultsmentioning
confidence: 99%
“…Since this test is evaluating a short‐term effect with a high dose rate that minimizes the annealing, the result shows the worst case for the low dose rate environment in space. Furthermore, Laird et al [] tested a 30 μm reach‐through APD up to 10 Mrad and showed that there was no change found in the multiplication factor.…”
Section: Avalanche Photodiodesmentioning
confidence: 99%
“…Since this test is evaluating a short-term effect with a high dose rate that minimizes the annealing, the result shows the worst case for the low dose rate environment in space. Furthermore, Laird et al [2006] tested a 30 μm reach-through APD up to 10 Mrad and showed that there was no change found in the multiplication factor. Becker et al [2003] showed with ∼50 MeV protons that the increase of leakage current was basically due to the displacement damage in the drift region.…”
Section: Radiation Tolerancementioning
confidence: 99%
See 1 more Smart Citation